FRASA DAN KLAUSA DALAM KATA POLISINTESIS PADA BAHASA TOLAKI - Pehala, Ilfan Askul (Center of Language and Cultural Studies, 2017)
This study examines the descriptions of phrases and sentences in the polysynthesis words. Sources of data of this study polyshyntesis words in Tolaki Language. Data were collected using observation and interview. Data were anlyzed using descriptive qualitative of formal and informal techniques. The study revealed that: (1) construction of phrases and sentences in the polyshyntesis words, (2) kinds of phrases in the polyshinthesis words, (3) functions, roles, and categories of clauses in the polysunthesis words, and (4) polysinthesis occured due to lapses or changes of mofphology of the Tolaki speakers